2022
DOI: 10.1007/s40506-022-00258-z
|View full text |Cite
|
Sign up to set email alerts
|

Updates in the Pharmacologic Prophylaxis and Treatment of Invasive Candidiasis in the Pediatric and Neonatal Intensive Care Units

Abstract: Purpose of review The goal of this review was to provide an update on the prevention and treatment options for invasive candidiasis (IC) in the neonatal intensive care unit (NICU) and pediatric intensive care unit (PICU). Recent findings Studies have further validated the use of fluconazole for IC prophylaxis among high-risk patients in the NICU. It remains unclear if prophylaxis leads to resistance development and the ideal dosage regimen is still not cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Prophylactic fluconazole and oral nystatin have both proven to be successful in the prevention of neonatal IFI. Although there is robust evidence supporting the effective and safe use of fluconazole as antifungal prophylaxis, concerns regarding the potential development of antifungal resistance limits its universal use [ 44 ]. A recent nationwide retrospective study in Japan reported that only 43% of medical facilities routinely prescribed antifungal prophylaxis for high-risk neonates [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic fluconazole and oral nystatin have both proven to be successful in the prevention of neonatal IFI. Although there is robust evidence supporting the effective and safe use of fluconazole as antifungal prophylaxis, concerns regarding the potential development of antifungal resistance limits its universal use [ 44 ]. A recent nationwide retrospective study in Japan reported that only 43% of medical facilities routinely prescribed antifungal prophylaxis for high-risk neonates [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, Amphotericin B deoxycholate or liposomal amphotericin B are recommended as first-line therapies for invasive fungal infections in neonates, but their use can be limited by nephrotoxicity [ 18 ]. Fluconazole is recommended as a second-line drug, but hepatotoxicity and azole resistance can limit its use [ 16 , 19 ]; furthermore, fluconazole prophylaxis is recommended against invasive candidiasis in very low and extremely low-birth-weight preterm neonates or in those carriers of central venous catheters [ 20 , 21 , 22 , 23 ]. When a fungal infection is suspected in a neonate who is already receiving fluconazole, a different salvage therapy is needed.…”
Section: Discussionmentioning
confidence: 99%
“…To date, micafungin is the only echinocandin that has been approved by the European Medicines Agency (EMA) for use in neonates [ 17 ] and, as explained, recently it has also been approved by the US Food and Drug Administration (FDA) for use in infants less than four months old [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current data on the appropriateness and benefits of neonatal antifungal prophylaxis suggest a more optional, customized and risk-based approach in NICUs. 13…”
Section: Neonatal Critically Ill Patientsmentioning
confidence: 99%
“…11 Current evidence on the association between the use of antifungal prophylaxis in neonates and subsequent development of antifungal resistance is hampered by differences in local fungal epidemiology and study methodologies (ie, sample size). 13…”
Section: Neonatal Critically Ill Patientsmentioning
confidence: 99%